Iteration complexity on the generalized Peaceman–Rachford splitting method for separable convex programming. (2nd September 2019) - Zhang, Xue-Qing; Peng, Jian-Wen; Yao, Jen-Chih
ABSTRACT: Recently, a generalized version of Peaceman–Rachford splitting method (GPRSM) for solving a convex minimization model with a general separable structure has been proposed and its global convergence has been proved by Sun and Liu. In this paper, we establish the worst-case O ( 1 / t ) convergence rate for the GPRSM in both the ergodic and a nonergodic senses, then we give some numerical results to demonstrate the convergence rate of the GPRSM.